PENERAPAN METODE SCAFFOLDING PADA PEMBELAJARAN SENI BUDAYA UNTUK MENINGKATKAN KEMAMPUAN KOGNITIF DAN KETERAMPILAN PESERTA DIDIK KELAS VII A SMPN 4 MALANG - Afrida Rusmila Dewi (Universitas Negeri Malang, 2024)
Vygotsky stated that the development of individual abilities is divided into two levels, namely the level of actual development and the level of potential development. The majority of class VII A students at SMPN 4 Malang are still at the level of potential development which is characterized by an inability to understand design teaching materials in arts and culture subjects independently. The aim of this research is to improve students' cognitive abilities and skills through the application of the scaffolding method. The scaffolding method is guidance given by teachers to students during learning which can lead them to reach their actual development stage. This research uses a qualitative approach. The methods used in this research are literacy studies and field observations. Literacy studies are carried out by analyzing several reference sources such as books, articles or journals. Field observations were carried out by observing the application of the scaffolding method directly over a certain period of time. Based on the data obtained through this research, the application of the scaffolding method is able to help students achieve learning goals more effectively and optimally.